Modeling Teacher Commitment by Preserving Local Wisdom and Strengthening Organizational Support - Hayatullisma, Gina; Hardhienata, Soewarto; Suhendra, Suhendra (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aims to examine how strengthening teachers' organizational commitment can be achieved through the preservation of local wisdom and the strengthening of organizational support. The main focus of this study is on permanent teachers at the SMP Sekolah Penggerak Foundation School located in Bogor Regency. Based on the sample calculation technique, the number of samples was set at 215 respondents. Path Analysis and SITOREM Analysis are combined research methods that combine Path Analysis with SITOREM Analysis to reinforce the results. The method used mix metode in this study is the POP-SDM (Organizational Development and Human Resource Management) method, which allows researchers to identify the factors that influence teacher commitment comprehensively. Primary data: Data obtained from questionnaires distributed to a number of teachers at private vocational high schools (SMK) in the Center of Excellence in Bogor Regency, West Java. Secondary data: Data obtained from the, which are accessible to the public. This study found that local wisdom, which includes the values and cultural practices that exist in the local community, plays an important role in increasing teachers' sense of responsibility and loyalty to the organization. In addition, strengthening organizational support, which consists of providing adequate facilities, recognizing teachers' contributions, and empowering them in the decision-making process, also strengthens their commitment to work more optimally. The results of this study provide important contributions to the development of educational policies that consider local and organizational contexts, as well as recommendations for school administrators and educational institutions to create a supportive work environment that values local wisdom. The uniqueness of this study lies in the use of the POP-SDM approach, which integrates local and organizational aspects to strengthen teacher commitment in schools in Bogor Regency.